N-Cadherin Expression Is Associated with Acquisition of EMT Phenotype and with Enhanced Invasion in Erlotinib-Resistant Lung Cancer Cell Lines - Zhang, Xiaoju; Liu, Guangzhi; Kang, Yi; Dong, Zhaogang; Qian, Qiyu; Ma, Xitao (PloS one, 2013)
The epidermal growth-factor receptor tyrosine kinase inhibitors have been effective in non-small cell lung cancer patients. However, acquired resistance eventually develops in most patients despite an initial positive response. Emerging evidence suggests that there is a molecular connection between acquired resistance and the epithelial-mesenchymal transition (EMT). N-cadherin is involved in the EMT and in the metastasis of cancer cells. Here, we analyzed N-cadherin expression and function in erlotinib-resistant lung cancer cell lines. H1650 cell lines were used to establish the subline resistant to erlotinib(H1650ER). Then, induction of the EMT was analyzed using immunostaining and western blots in H1650ER cells. N-cadherin expression in the resistant cells was examined using FACS and western blot. In addition, an invasion assay was performed to characterize the resistant cells. The effects of N-cadherin on cell proliferation and invasion were analyzed. The association of N-cadherin expression with the EMT phenotype was investigated using immunohistochemical analysis of 13 archived, lung adenocarcinoma tissues, before and after treatment with erlotinib. In H1650ER cells, N-cadherin expression was upregulated, paralleled by the reduced expression of E-cadherin. The marked histological change and the development of a spindle-like morphology suggest that H1650ER cells underwent an EMT, accompanied by a decrease in E-cadherin and an increase in vimentin. A change in the EMT status between pre-and post-treatment was observed in 11 out of 13 cases (79%). In biopsies of resistant cancers, N-cadherin expression was increased in 10 out of 13 cases. Induction of the EMT was consistent with aggressive characteristics. Inhibition of N-cadherin expression by siRNA was tested to reduce proliferation and invasion of H1650ER cells in vitro. Our data provide evidence that induction of the EMT contributes to the acquired resistance to EGFR-TKIs in lung cancer. It suggests that N-cadherin is a potential molecular target in the treatment of NSCLC.